2016
DOI: 10.1371/journal.pntd.0005235
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a Hidden Enemy: Pyriproxyfen Autodissemination Strategy for the Control of the Container Mosquito Aedes albopictus in Cryptic Habitats

Abstract: BackgroundThe Asian tiger mosquito, Aedes albopictus, is a vector of dengue, Chikungunya, and Zika viruses. This mosquito inhabits a wide range of artificial water-holding containers in urban and suburban areas making it difficult to control. We tested the hypothesis that female-driven autodissemination of an insect growth regulator could penetrate cryptic oviposition habitats difficult to treat with conventional insecticidal sprays.MethodologyOviposition preferences of Ae. albopictus females for open and cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
(41 reference statements)
4
44
0
Order By: Relevance
“…aegypti in our study. This result was similar to those of Unlu et al [19] and Chandel et al [20], in which the PPF residual in water samples taken from sentinel cups ranged from 4 to 11 ng/L, causing more than 70% pupal mortality in Ae. albopictus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…aegypti in our study. This result was similar to those of Unlu et al [19] and Chandel et al [20], in which the PPF residual in water samples taken from sentinel cups ranged from 4 to 11 ng/L, causing more than 70% pupal mortality in Ae. albopictus.…”
Section: Discussionsupporting
confidence: 91%
“…The concentration of PPF product used in our study (0.01%) was relatively low compared to that in other studies, and the result showed that the mean EI% was 37% one month post-spraying. This EI% observed in our field trial was similar to the value from a study by Chandel et al, in which the mean percentage of pupal mortality was 29.7% among cryptic sentinel cups [20]. Although the low concentration of PPF used in the field may have a weak EI effect, it would rarely harm untargeted creatures, making it an ecofriendly strategy to control mosquitoes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The combination of larviciding and adulticiding at half the label rate was followed by a second adulticiding also at half the label rate within 2–4 days, depending on weather conditions, using truck‐mounted ULV sprays . The purpose of this additional adulticiding campaign was to increase the efficacy of intervention efforts by targeting the adults that emerged because the larvae were already late fourth instar or pupae at the time of the intial larviciding event . We repeated pyriproxifen larviciding and pyrethroid adulticiding on 16 September 2011 when the mean number of Ae .…”
Section: Methodsmentioning
confidence: 99%
“…37 The purpose of this additional adulticiding campaign was to increase the efficacy of intervention efforts by targeting the adults that emerged because the larvae were already late fourth instar or pupae at the time of the intial larviciding event. 38,39 We repeated pyriproxifen larviciding and pyrethroid adulticiding on 16 September 2011 when the mean number of Ae. albopictus was five or more (males and females), which was a pre-set intervention threshold for this study.…”
Section: Truck-mounted Larviciding and Adulticidingmentioning
confidence: 99%